A Functional Analysis of Inversion in English Sentences - Muhammad Zaki Pahrul Hadi; Syamsurrijal Syamsurrijal (Lingua Susastra, 2022)
Inversion is defined as the appearance of the main verb before the subject of an utterance. Using descriptive qualitative approach, this research analyzed phenomenon of language which happens at present. The object of this research is the inversion systems in English. The sources of the data are taken from English books, papers and other resources such as TOEFL test preparation books that related to the topic. In gathering data, the researcher used two techniques namely teknik catat (noting technique) and teknik pisah (separating technique). The result of analyses showed that there are six types of inversion system in terms of forms namely; inverting the main verb to subject, inverting auxiliary verb to subject, adding the auxiliary verb preceding the subject, Inverting the adverb and the subject, Inverting the preposition and the subject, Sentence beginning with there. Meanwhile types of inverted sentence are classified into six. They are interrogative sentence, conditional sentence, statement, comparative sentence, exclamation, reporting sentence. In term of function, there are three functions of inversion namely, emphasizing the negative expression, emphasizing the time expression, and as a variation.